Antitumor progression potential of morusin suppressing STAT3 and NFκB in human hepatoma SK-Hep1 cells. Issue 2 (22nd January 2015) - Lin, Wea-Lung; Lai, Deng-Yu; Lee, Yean-Jang; Chen, Nai-Fang; Tseng, Tsui-Hwa
Graphical abstract